Pesan Komunikasi Pada lagu Inochi Ni Kirawarete Iru - Aditiya, I Wayan Deva; Putra, Kharis Agung Eka; Lindayani, Luh (Jurnal Pendidikan Bahasa Jepang Undiksha, 2024)
This research aims to determine the communication message in the song Inochi ni Kirawarete iru (hated by life itself). The song Inochi ni Kirawarete iru is a work by Kanzaki Iori sung by Hatsune Miku. This song was released on August 6, 2017, on the album entitled Hakushi. This research uses John Fiske's communication theory as a theoretical basis. According to John Fiske, communication theory explains how communication is conveyed and meaning is formed. They are using a descriptive approach and a note-taking method. Data was obtained from the official Hatsune Miku YouTube. The result of this research is that the concept of this song is under the title, namely someone who is hated by life itself. This song shows humans' strange, selfish nature and sense of hopelessness.